LEARNING STATES OF MATTER USING PhET MOBILE APPLICATION TO IMPROVE STUDENTS' UNDERSTANDING AND INTEREST - Theresia Enggraeni Siburian, - (2018)
PhET (Physics Education Technology) is a simple animated illustration of the interactive classroom. The aim of the media was to provide realistic interactive science simulations. This research investigated the implementation of PhET mobile application on students' understanding and interest in learning States of Matter topic. The method used in this research was pre experimental with one group pre-test post-test design. The research conducted in one of private Junior High School located in Bandung with number of students (n=121) of 7th grade students. The sampling technique used was purposive sampling. The quantitative data of this research was obtained through objective test in the pre-test and post-test, meanwhile the qualitative data was obtained through Likert scale in the questionnaire. The result shows that the students who learn States of Matter topic with PhET mobile application have higher both improvement in understanding (g= 0.61) and interest (very high interest) than without PhET mobile application as teaching media. According to analysis result, there is a correlation between students' understanding and interest in learning the States of Matter topic uses PhET mobile application. The criterion of correlation is fair correlation (0.25-0.50).;---PhET (Physics Education Technology) adalah ilustrasi animasi sederhana untuk kelas interaktif. Tujuan media ini adalah menyediakan simulasi sains interaktif yang realistis. Penelitian ini bertujuan untuk menyelidiki penggunaan aplikasi seluler PhET pada pemahaman siswa dan ketertarikan dalam pembelajaran Wujud Zat. Metode yang digunakan dalam penelitian ini adalah pre eksperimen dengan one group pre-test post-test design. Penelitian dilakukan pada satu Sekolah Swasta Menengah Pertama yang berlokasi di Bandung dengan jumlah siswa kelas 7 sebanyak 121 siswa (n=121). Teknik pengambilan sampel yang digunakan adalah purposive sampling untuk menentukan partisipan yang digunakan sebagai kelas eksperimen dengan penggunaan aplikasi seluler PhET dalam pembelajaran Wujud Zat. Data kuantitatif dari penelitian ini didapatkan melalui tes objektif yang diberikan pada pre-test dan post-test, sedangkan kualitatif data didapatkan melalui interest scale rubric dan kuisioner. Hasil penelitian menunjukkan bahwa siswa yang belajar topic Wujud Zat menggunakan aplikasi seluler PhET lebih meningkat dalam pemahaman konseptual (g= 0.61) dan minat (minat yang sangat tinggi) daripada tanpa aplikasi seluler PhET sebagai media pembelajaran. Sesuai dengan hasil analisis, terdapat hubungan antara pemahaman konseptual dan minat siswa dalam pembelajaran Wujud Zat menggunakan aplikasi seluler PhET. Kriteria korelasi dalam penelitian ini adalah korelasi cukup (0.25-0.50).